Histopathological impact of Redox-responsive methacrylamide based micellar nanoparticles on Orthotopic Models of Triple Negative Breast Cancers - Fatemeh Mehradnia; Cara Moloney; Robert Cavanagh; Amanda K Pearce; Alison Ritchie; Philip Clarke; Ruman Rahman; Asmaa Ibrahim; Anna M. Grabowskab; Cameron Alexander (University of Huddersfield Press, 2022)
The therapeutic efficacy of anticancer nanocarriers is highly dependent on their size, shape, targeting ability, and stimuli-responsiveness. Herein, we studied the in vivo therapeutic efficacy of Doxorubicin (Dox) loaded redox responsive micellar-like nanoparticles (MNPs)based on linear 2-hydroxypropyl methacrylamide (HPMA) via histopathological evaluations. The therapeutic efficacy of DOX-loaded micellar-like Nanoparticles significantly improved while the side effects reduced as confirmed by histopathological examinations. H&E and tunnel staining of tumor tissues indicated the higher population of apoptotic tumor cells in both treatment groups containing DOX. These redox responsive crosslinked HPMA-based micellar-like nanoparticles with acceptable therapeutic efficacy and apoptosis induction in cancerous cells proved to be promising nanomedicine for breast cancer chemotherapy.